Hubungan Tingkat Kecukupan Protein Hewani dan Kalsium, Tingkat Stres, Serta Kebiasaan Olahraga Terhadap Derajat Nyeri Dismenore Primer Siswi SMAN1 Kota Sukabumi: Hubungan Tingkat Kecukupan Protein Hewani, Kalsium, Tingkat Stres serta Kebiasaan Olahraga terhadap Derajat Nyeri Dismenorea Primer Siswi SMAN 1 Kota Sukabumi - Dian Rahayuningsih; Vitria Melani; Dudung Angkasa; Harna Harna; Nadiyah Nadiyah (Universitas Airlangga, 2023)
Background: Primary dysmenorrhea during the menstruation period can cause uncomfortable conditions, reduction in productivity and study concentration, and daily activities in adolescents. Calcium source and animal protein consumption may reduce the pain intensity of primary dysmenorrhea. In addition, normal stress levels and regular exercise habits can regulate the release of hormones that control pain intensity. Objectives: This study aims to analyze the correlation between animal protein consumption, calcium adequacy level, stress level, exercise habits, and primary dysmenorrhea pain level in female students of SMAN 1 Sukabumi City. Methods: This quantitative study used an observational study design with a Cross-Sectional approach. Simple random sampling was taken from twelfth-grade science classes with 62 female students in SMAN 1 Sukabumi City. Data collection was performed through interviews using Google Forms and Zoom. The instruments used were SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire), DASS 42 questionnaire (Depression Anxiety Stress Scale), Wong-Baker Pain scale, and exercise habit questionnaire. Bivariate analysis was done using the Chi-Square test with α=0.05. Results: There was a correlation between the level of calcium adequacy and the scale of primary dysmenorrhea pain in female students of SMAN 1 Sukabumi City (P<0.05), and no significant correlation between the level of adequacy of animal protein consumption, exercise habit, the level of stress and the scale of primary dysmenorrhea pain (P>0.05). Conclusions: Respondents with sufficient calcium levels can lower the degree of primary dysmenorrhea pain. Therefore, meeting the calcium requirement to prevent menstrual pain is recommended.